2021
DOI: 10.1371/journal.pmed.1003567
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography and magnetic resonance imaging in experimental human malaria to identify organ-specific changes in morphology and glucose metabolism: A prospective cohort study

Abstract: Background Plasmodium vivax has been proposed to infect and replicate in the human spleen and bone marrow. Compared to Plasmodium falciparum, which is known to undergo microvascular tissue sequestration, little is known about the behavior of P. vivax outside of the circulating compartment. This may be due in part to difficulties in studying parasite location and activity in life. Methods and findings To identify organ-specific changes during the early stages of P. vivax infection, we performed 18-F fluorodeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…In malaria volunteer infection studies, despite the low parasite counts, participants still experience a significant inflammatory response, with elevated levels of IFN-γ and IL-6 [ 65 67 ] potentially contributing to inhibition of erythropoiesis [ 68 ]. Additional contributors to the loss of unparasitized cells in acute clinical malaria include haemolysis, decreased red blood cell deformability, antibody and complement binding to erythrocytes, loss of complement regulatory proteins on the surface of unparasitized erythrocytes [ 69 ] and increase in splenic size [ 70 ] with associated splenic clearance of uninfected erythrocytes [ 71 ]. However, the role of these processes in low-parasitaemia infections such as volunteer infection studies has been more difficult to define [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In malaria volunteer infection studies, despite the low parasite counts, participants still experience a significant inflammatory response, with elevated levels of IFN-γ and IL-6 [ 65 67 ] potentially contributing to inhibition of erythropoiesis [ 68 ]. Additional contributors to the loss of unparasitized cells in acute clinical malaria include haemolysis, decreased red blood cell deformability, antibody and complement binding to erythrocytes, loss of complement regulatory proteins on the surface of unparasitized erythrocytes [ 69 ] and increase in splenic size [ 70 ] with associated splenic clearance of uninfected erythrocytes [ 71 ]. However, the role of these processes in low-parasitaemia infections such as volunteer infection studies has been more difficult to define [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, in the P. vivax infection studies, the calculation of total parasite burden prior to antimalarial treatment did not account for parasite sequestration. Recent studies have suggested that in chronic P. vivax infection, a very high proportion of parasitized erythrocytes are sequestered in the spleen [ 52 ], and it has also been shown that splenic accumulation may occur even in early P. vivax infection [ 70 ]. It is possible that this may in part explain the low contribution of peripheral parasitized cells to the malaria-attributable erythrocyte loss, in this study and in others [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Splenic trauma or rupture are rare during clinical malaria and performing splenic studies in untreated clinical disease may require indirect, noninvasive evaluation. Recent positron emission tomography and magnetic resonance imaging in experimental human volunteer infection studies indicate greater splenic tropism and metabolic activity in early Pv infection compared to Pf [82], suggesting that splenic accumulation of Pv occurs even early in infection. Our cohort requiring splenectomy may also not be representative of the wider population.…”
Section: Plos Medicinementioning
confidence: 99%
“…Non-human primate PET studies have identified intense FDG uptake associated with accumulation of parasites in the spleen 22 , and we have recently described enhanced splenic uptake in the same population of participants following both experimental P. falciparum and P. vivax infection. In the latter study splenic uptake was significantly increased in P. vivax compared to P. falciparum infection , suggesting splenic tropism with this species 16 , 23 . In the current study, interval change in radiotracer uptake was largely uniform across all brain subregions, irrespective of blood supply or white–grey matter differentiation for all participants.…”
Section: Discussionmentioning
confidence: 58%